The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jace.18541
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cation disorder and oxygen vacancies in Li‐rich Li2TiO3

Abstract: Li 2 TiO 3 has a broad stoichiometric range and wide application prospects such as cathode, tritium breeder, and microwave dielectric materials. Particularly, Li 2 TiO 3 shows a faster tritium release performance and exceptional chemical and radiation stabilities, making it one of the most promising solid breeder materials. Li-rich Li 2 TiO 3 has been developed for years as an advanced breeder material due to its enhanced tritium production and better stability in hydrogen atmosphere.However, the defect chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Their Zn–O and Ga–O bond lengths and cell volume as a function of Ni 2+ concentration were calculated and are listed in Table 1. It is found that the bond lengths related to Zn–O, Ga–O, and unit‐cell volume decrease with increasing Ni 2+ concentration due to the ionic radius of Ni 2+ being smaller than that of Zn 2+ , 19 further proving that Ni 2+ ions tend to replace Zn 2+ ions in ZGGO nanoparticles.…”
Section: Resultsmentioning
confidence: 95%
“…Their Zn–O and Ga–O bond lengths and cell volume as a function of Ni 2+ concentration were calculated and are listed in Table 1. It is found that the bond lengths related to Zn–O, Ga–O, and unit‐cell volume decrease with increasing Ni 2+ concentration due to the ionic radius of Ni 2+ being smaller than that of Zn 2+ , 19 further proving that Ni 2+ ions tend to replace Zn 2+ ions in ZGGO nanoparticles.…”
Section: Resultsmentioning
confidence: 95%
“…The intensity ratio of peak A and B, I A /I B , represents the degree of long-range cation ordering. 38,39 Although the I A /I B ratios were 2.4 and 0.0 in the simulated patterns from the perfect crystals of β-and γ-Li 2 TiO 3 , the ratios from the samples before and after irradiations were 2.0…”
Section: Discussionmentioning
confidence: 91%
“…This peak is designated as peak B in this paper, which is derived from the main peak of γ‐Li 2 TiO 3 from (2 0 0) plane as well as (1 3 3) and (2 0 2) planes in β‐Li 2 TiO 3 . The intensity ratio of peak A and B, I A / I B , represents the degree of long‐range cation ordering 38,39 . Although the I A / I B ratios were 2.4 and 0.0 in the simulated patterns from the perfect crystals of β‐ and γ‐Li 2 TiO 3 , the ratios from the samples before and after irradiations were 2.0 and 1.0, respectively.…”
Section: Discussionmentioning
confidence: 99%